Experiences of Anti-Blackness in Islamic Educational Spaces: Implications for Islamic Teacher Education - Shyla González-Doğan (MDPI AG, 2023)
This paper is an initial examination of anti-Blackness within a specifically Muslim context, and it presents the experiences of some Black community members who attended one U.S. city's primary local mosque's weekend school program and who either attended or had children who attended the city's sole Islamic school. During this ethnographic project, 18 participants who identified as part of the Muslim community of the city were interviewed; semi-structured interviews and snowball sampling were used to obtain data. Research participants included parents of children in the Islamic school or weekend school program at the affiliated mosque, former students of the Islamic school or the mosque's weekend school program, and former or current leaders in the community. The findings demonstrate that anti-Blackness in Islamic community spaces often manifests through the targeting of Black children for perceived misbehavior in educational spaces and through practices of exclusion toward Black community members. The findings also indicate that there is a need for increased education and training related to anti-Blackness and a need for the implementation of an anti-racist pedagogy in Islamic educational settings.